Pengembangan Kewirausahaan di Universitas Muhammadiyah Pontianak - Farida Farida; Edy Suryadi; Samsuddin Samsuddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Entrepreneurship Development Program (PPK) at Muhammadiyah Pontianak University is a program with a mission to produce new entrepreneurs, through an integrated program involving students managing PPK and resource persons. PPK Muhammadiyah University Pontianak activities include: management training, business skills with the Start and Improve Your Business (SIYB) method consisting of Generate Business Idea (GBI), Start Your Business (SYB) and modules Improve Your Business (IYB) covering Marketing, Financial Planning, Bookkeeping, Purchasing, Stock Control and Financing in the context of empowering the potential of entrepreneurship for students. Students who have started entrepreneurship, Student Entrepreneurship Student Creativity Program (PKMK), alumni who are interested in or are just starting a business can perfect their previous entrepreneurial activities, to increase its business. Manager of PPK Muhamamdiyah University Pontianak will explore the types of tenant business commodities according to their talents and interests. The PPK program service unit at the Muhammadiyah University of Pontianak each year will produce at least five new science-based independent entrepreneurs per year who are ready to move in the community. The recruitment of PPK tenants is carried out through synergy with the Muhamamdiyah University Student Affairs in Pontianak to recruit students who get PKMK or other PKM, students and alumni who are pioneering businesses